An impact assessment of the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 - Chamlin, Mitchell B. (Journal of crime and justice, 2019)
On 22 August 1996, President Bill Clinton signed into law the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (House Bill, 3734). According to the final version of this legislation, this reduction in the size and cost of aid to the poor was to be accomplished by reducing the number of births to unmarried women, the number of births to teens, and by providing the motivation and means to enter the labour force. The interrupted time series analyses indicate that the implementation of the Temporary Assistance for Needy Families [TANF] welfare programme did produce a substantial and lasting decline in the number of welfare recipients and in the birth rate per 1,000 women aged 15 to 19. However, there is no evidence that it did so because of its effect on the birth rate of unmarried women, household structure of families, or participation in the labour force.